The Influence of the Use of PhET Simulation and Online Practical Flexibility on Physics Learning Outcomes of Students at MTs Baiturrahman NW Pemepek in the Digital Era - Nopianti (International Journal of Contextual Science Education, 2026)
This study aims to describe the initial stages of a study on the effect of the use of PhET simulation media and the flexibility of online practicums on physics learning outcomes of students at MTs Baiturrahman NW Pemepek in the digital era. The background of this study is based on the need to integrate simulation-based learning technology into the physics teaching and learning process to make it more interactive and effective. This study uses a quantitative approach with a quasi-experimental method involving two groups of students as research subjects. In the initial stage, research activities focused on developing instruments and collecting initial data through five multiple-choice questions to measure students' initial abilities before being given treatment using PhET simulation media. The data obtained were analyzed descriptively to describe students' initial level of understanding of physics material. Preliminary results show variations in the level of concept mastery among students, which will later become the basis for implementing simulation media and online practicums in the next stage. This study is expected to contribute to the development of digital learning strategies in the madrasah environment.